Manajemen Risiko pada Pelaksanaan Pekerjaan Bendung Batang Pagian Kabupaten Dharmasraya - Junaidi, Junaidi; Zarfinal, Zarfinal; Anif, Bahrul (Jurnal Talenta Sipil, 2024)
Risks in construction project work are events or occurrences that are uncertain but can have a positive or negative impact on the sustainability of a project. In this research, the author carried out an analysis of risks, impacts and risk responses caused by failure in the construction work of the Batang Pangian weir construction project. The aim is to identify potential risks and the impact of risks that occur in the implementation of the Batang Pagian weir project work, as well as to obtain risk responses that can be carried out. The research was conducted qualitatively through field surveys and interviews with respondents involved in the field. Next, a risk assessment was carried out referring to the Godfrey development method. Based on the results of research analysis, it was found that the flood disaster was the main trigger for failure in the implementation of construction work for the Batang Pangian Dam. The impact of the flood disaster resulted in the main irrigation canal being closed so that water flow became obstructed and had an impact on the agricultural sector. The risk responses carried out include creating alternative channels and conducting outreach to the community regarding this problem.